Revelação do diagnóstico de HIV/AIDS na infância : impactos, cotidiano e perspectivas de jovens infectados verticalmente - Negrini, Silvia Fabiana Biason de Moura (2017)
Children living with HIV / AIDS are growing and demanding new interventions and health care strategies, such as the need to know their clinical status. Recent national and international studies have sought a better understanding of the issue of disclosure of HIV / AIDS diagnosis to vertically infected children and adolescents and their consequences. The objective of this research was to understand about the contributions and limits of a diagnostic disclosure process to children infected vertically by HIV / AIDS, developed by a multidisciplinary team of a tertiary hospital and approach, from the perspective of these current young people Social relations, daily challenges and future expectations. To do so, two studies were carried out: Study 1 aimed to identify the variations in CD4 and Viral Load rates of children infected vertically by HIV / AIDS, after participating in the process of diagnosis, developed by a multidisciplinary team of a hospital Ternary school in the interior of São Paulo - Brazil, as well as if this variation is associated with variables such as: gender, age, family composition and frequency in the groups, both of the children and the parents, and Study 2 aimed to investigate the impacts in daily life, the Challenges and future expectations, after the moment of revelation and in the present, from the perspective of young people, children at the time of revelation. The research was approved by the Research Ethics Committee of the Hospital das Clínicas of the Medical School of Ribeirão Preto - USP and both studies were carried out in this place. For Study 1, data were collected in 65 charts of young people, children at the time of diagnosis. The information was recorded in a specific form and stored in a database. The results are presented in a descriptive and analytical way and, to verify the association between the variables, the "Fisher's exact test" was used. In Study 2, 17 young people, aged between 16 and 24 years participated, being 10 females and 7 males. All participants were infected with HIV by vertical transmission, they were part of the diagnostic disclosure process focused on this study, and they continue to be followed at the same health service. The instruments used were an identification form and a semi-structured interview script. For the data analysis, the Collective Subject Discourse (DSC) technique was used. The results of Study 1 show that there was an association between the participation of the caregivers in the group of the diagnostic process and the improvement in the CD4 rates of the children, besides the stabilization in the levels of viral load and CD4, after the diagnosis was revealed. The results of Study 2 point to the benefits reported by the participants regarding disclosure by the family associated with the UETDI disclosure process. Nevertheless, it was verified that it is during adolescence that the concreteness of the diagnosis is placed in their lives and, as a daily challenge, reveal the common presence of social prejudice imposed on young people with HIV. It discusses the relevance of diagnostic disclosure processes and highlights the relevance of the disclosure proposal evaluated in this study. Suggestions are suggested for the improvement of the process, especially regarding the resumption of the diagnosis and its implications in adolescence. Furthermore, the challenge of coping with prejudice as collective responsibility and with the concrete involvement of public policies is discussed.